2022
DOI: 10.3390/rs14030602
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Accuracy of MODIS MCD64A1 C6 and FireCCI51 Burned Area Products in Mediterranean Ecosystems

Abstract: The catastrophic impact of wildfires on the economy and ecosystems of Mediterranean countries in recent years, along with insufficient policies that favor disproportionally high funding for fire suppression, demand a more comprehensive understanding of fire regimes. Satellite remote sensing products support the generation of relevant burned-area (BA) information, since they provide the means for the systematic monitoring of large areas worldwide at low cost. This research study assesses the accuracy of the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 49 publications
(87 reference statements)
2
16
0
2
Order By: Relevance
“…Among optical sensor data, the BA-S2L8 datasets for the years 2018 and 2020, and BA-MAPBIOMAS, for the year 2019, presented the highest rates, being, respectively, 13% and 56% for BA -S2L8 and 50% for BA-MAPBIOMAS. We emphasize that the overlaps focused on polygons of burned areas smaller than 6.5 hectares, demonstrating the high spatial similarity between the datasets for small fire areas, despite the BA-MCD64A1 not being the best sensor to detect burns more minor than 100 hectares (Katagis and Gitas, 2022).…”
Section: Resultsmentioning
confidence: 95%
“…Among optical sensor data, the BA-S2L8 datasets for the years 2018 and 2020, and BA-MAPBIOMAS, for the year 2019, presented the highest rates, being, respectively, 13% and 56% for BA -S2L8 and 50% for BA-MAPBIOMAS. We emphasize that the overlaps focused on polygons of burned areas smaller than 6.5 hectares, demonstrating the high spatial similarity between the datasets for small fire areas, despite the BA-MCD64A1 not being the best sensor to detect burns more minor than 100 hectares (Katagis and Gitas, 2022).…”
Section: Resultsmentioning
confidence: 95%
“…The developed mathematical model enables modernization or replacement of systems for predicting forest fire danger [77][78][79][80]. In addition, the technologies of mathematical modeling, geoinformation technologies, and remote sensing data can be integrated into a big multifunctional system [81][82][83][84].…”
Section: Discussionmentioning
confidence: 99%
“…This study makes use of the MODIS FireCCI51 fire data (Chuvieco et al, 2018a ). This product has been extensively validated for wildfires and larger burns (Hall et al, 2021 ), is shown to have a higher detection of smaller fires (< 1 km 2 ) compared to other products (Katagis & Gitas, 2022 ), and has comparable accuracy in detecting tropical peatland fires (Vetrita et al, 2021 ). Despite this, limitations of the MODIS burned area data have been documented in the literature (Alves et al, 2018 ; Chuvieco et al, 2018b ; Ying et al, 2019 ), with omission errors up to 72% (Boschetti et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%